Constraints of sedimentary structures on key parameters of shale gas reservoirs: A case study of the Wufeng and Longmaxi formations of the Ordovician‐Silurian transition in Luzhou area, Sichuan Basin, southwestern China. (21st September 2021) - Liao, Jijia; Zhao, Ning; Chen, Yang; Tang, Hongming; Zheng, Majia; Wu, Wei; Luo, Chao; Li, Changsheng; Leng, Yijiang
Abstract : There are various sedimentary structures developed in the black shales of the Upper Ordovician Wufeng Formation and the Lower Silurian Longmaxi Formation in Luzhou area, southern Sichuan Basin, southwestern China. In order to evaluate the controlling effects of sedimentary structures on the key parameters of shale reservoir properties, collected classification of sedimentary structures, scanning electron microscope observation, analysis of shale fabric and porosity characteristics, low‐pressure nitrogen adsorption, methane isothermal adsorption, and conventional triaxial compression test were carried out based on shale samples from Wells A‐H1, B‐H1, C‐H1 and D‐H1 in the study area. The sedimentary structures recorded in these shales are categorized into five types: homogeneous bedding, weak horizontal bedding, strong horizontal bedding, discontinuous ripple bedding, and gravel‐bearing massive bedding. In general, the palaeo‐hydrodynamics and oxygen content of water columns were weak when homogeneous bedding shale was deposited. The organic matter is the most abundant and the total organic carbon content is up to 4.01% on average. The average quartz content is 43.5%, and the brittleness index is the highest. The porosity and adsorption capacity were the highest, with an average of 4.57% and 79.5 scf/ton, respectively. Combined with its mechanical properties of low Poisson's ratio and high Young's modulus, homogeneous bedding sedimentary structure is associated with the shale units possessing the highest organic matter abundance, the strongest reservoir property, and the best fracability, which is the priority target for exploration and development of the Wufeng to lower Longmaxi Formation in the Sichuan Basin, southwestern China. Abstract : The types of sedimentary structures of shale were categorized at the scale of thin slices. The influences of different sedimentary structures on total organic carbon, mineral types and compositions, storage and adsorption capacity and fracability of shale were assessed. The relationship between sedimentary structures and reservoir properties from two aspects of geology and engineering are also evaluated, in order to provide theoretical reference for the next exploration and development of shale gas reservoirs.